Ion track reconstruction in 3D using alumina-based fluorescent nuclear track detectors - Niklas, Martin Anthony; Bartz, J. A.; Akselrod, M. S.; Abdollahi, Amir; Jäkel, Oliver; Greilich, Steffen (Physics in medicine and biology, 2013)
Fluorescent nuclear track detectors (FNTDs) based on Al2O3: C, Mg single crystal combined with confocal microscopy provide 3D information on ion tracks with a resolution only limited by light diffraction. FNTDs are also ideal substrates to be coated with cells to engineer cell-fluorescent ion track hybrid detectors (Cell-Fit-HD). This radiobiological tool enables a novel platform linking cell responses to physical dose deposition on a sub-cellular level in proton and heavy ion therapies. To achieve spatial correlation between single ion hits in the cell coating and its biological response the ion traversals have to be reconstructed in 3D using the depth information gained by the FNTD read-out. FNTDs were coated with a confluent human lung adenocarcinoma epithelial (A549) cell layer. Carbon ion irradiation of the hybrid detector was performed perpendicular and angular to the detector surface. In situ imaging of the fluorescently labeled cell layer and the FNTD was performed in a sequential read-out. Making use of the trajectory information provided by the FNTD the accuracy of 3D track reconstruction of single particles traversing the hybrid detector was studied. The accuracy is strongly influenced by the irradiation angle and therefore by complexity of the FNTD signal. Perpendicular irradiation results in highest accuracy with error of smaller than 0.10°. The ability of FNTD technology to provide accurate 3D ion track reconstruction makes it a powerful tool for radiobiological investigations in clinical ion beams, either being used as a substrate to be coated with living tissue or being implanted in vivo.
Gesehen am 25.11.2021